Control of arginine metabolism in Neurospora: flux through the biosynthetic pathway. - Goodman, I (1980)
The flux into the arginine biosynthetic pathway of Neurospora crassa was investigated using a mutant strain lacking the ornithine-degrading enzyme ornithine aminotransferase (EC 2.6.1.13). Flux was measured by the increase in the sum of the radioactivity (derived from [14C]glutamic acid) in the ornithine pool, the arginine pool, and arginine incorporated into proteins. Complete cessation of flux occurred immediately upon the addition of arginine to the growth medium. This response occurred prior to expansion of the arginine pool. After short-term exposure to arginine (80 min), flux resumed quickly upon exhaustion of arginine from the medium. This took place despite the presence of an expanded arginine pool. Initiation of flux required approximately 80 min when the mycelia were grown in arginine-supplemented medium for several generations before exhaustion of the exogenous arginine. The arginine pool of such mycelia was similar to that found in mycelia exposed to exogenous arginine for only 80 min. The results are consistent with rapid onset and release of feedback inhibiton of arginine biosynthesis in response to brief exposure to exogenous arginine. The insensitivity of flux to the size of the arginine pool is consistent with a role for compartmentation in this regulatory process. The lag in initiation of flux after long-term growth in the presence of exogenous arginine suggests the existence of an additional regulatory mechanism(s). Several possibilities are discussed.